2021
DOI: 10.3390/cancers13081946
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Macrophages in Cancer Development and Therapy

Abstract: Macrophages are critical mediators of tissue homeostasis and influence various aspects of immunity. Tumor-associated macrophages are one of the main cellular components of the tumor microenvironment. Depending on their activation status, macrophages can exert a dual influence on tumorigenesis by either antagonizing the cytotoxic activity of immune cells or, less frequently, by enhancing antitumor responses. In most situations, TAMs suppress T cell recruitment and function or regulate other aspects of tumor imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(141 citation statements)
references
References 197 publications
3
106
0
Order By: Relevance
“…A recent review of about 300 studies on the prognostic implication of infiltrated M1 or M2 macrophage subtypes, concluded that while the M2 macrophages are associated with poor prognosis, the presence of the M1 macrophages corresponds with a favorable clinical outcome [ 30 ]. It is conceivable that by enhancing the recruitment of CD206 + CD163 + M2 macrophages, PSA facilitates an immunosuppressive TME characterized by upregulated Treg and suppressed dendritic cell pooling, extracellular matrix remodeling, and upregulation of “don’t eat me” signals [ 31 ]. Conversely, we posit that AIM, by enhancing the infiltration of CD80 + CD86 + M1 macrophages, activates adaptive immunity, enhances antigen presentation, represses the “don’t eat me” signal, and thus, reactivates anticancer immune activity [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review of about 300 studies on the prognostic implication of infiltrated M1 or M2 macrophage subtypes, concluded that while the M2 macrophages are associated with poor prognosis, the presence of the M1 macrophages corresponds with a favorable clinical outcome [ 30 ]. It is conceivable that by enhancing the recruitment of CD206 + CD163 + M2 macrophages, PSA facilitates an immunosuppressive TME characterized by upregulated Treg and suppressed dendritic cell pooling, extracellular matrix remodeling, and upregulation of “don’t eat me” signals [ 31 ]. Conversely, we posit that AIM, by enhancing the infiltration of CD80 + CD86 + M1 macrophages, activates adaptive immunity, enhances antigen presentation, represses the “don’t eat me” signal, and thus, reactivates anticancer immune activity [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that by enhancing the recruitment of CD206 + CD163 + M2 macrophages, PSA facilitates an immunosuppressive TME characterized by upregulated Treg and suppressed dendritic cell pooling, extracellular matrix remodeling, and upregulation of “don’t eat me” signals [ 31 ]. Conversely, we posit that AIM, by enhancing the infiltration of CD80 + CD86 + M1 macrophages, activates adaptive immunity, enhances antigen presentation, represses the “don’t eat me” signal, and thus, reactivates anticancer immune activity [ 30 , 31 ]. This would be consistent with the concomitant expression of AIM with FCGR2A, FCGR1A, ITGAM, and FCGR3A, all of which play essential roles in enhanced anticancer immune responses and are associated with good clinical outcomes [ 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…TAMs are critical components of the TME [ 116 ]. Macrophages are involved in numerous biological processes including tissue homeostasis, defense against pathogens and wound healing [ 117 , 118 ]. They originate from circulating monocytes and are transformed at sites of inflammation into activated M1 or M2 phenotypes.…”
Section: Sev-mediated Crosstalk Of Pdac and Associated Cells In The Tmementioning
confidence: 99%
“…Macrophages can be highly influential on tumour development through the induction of inflammation, stimulation of neoangiogenesis, immune suppression or induction of metastasis. Macrophages that populate a tumour’s surrounding environment (the tumour microenvironment (TME)) are referred to as tumour-associated macrophages (TAMs); we direct the reader to the very recent review by Cendrowicz et al [ 11 ] for a detailed description of the contribution of TAMs to the formation and development of tumours. Both clinical and experimental evidence has found that a high density of TAMs within a TME is strongly correlated with poor prognosis and reduced survival in a number of cancer types [ 12 ].…”
Section: Metabolic Hormones Modulate Macrophage Inflammatory Responsesmentioning
confidence: 99%